Investigating the Impact of Multiple Strategic Orientations and Strategic Flexibility on Product Innovation (Case Study: Knowledge-Based Companies in Kerman City) - Shahabi, Ellahe; Dehyadegari, Saeed; Shoukohian, Haniye (Management Strategies and Engineering Sciences, 2025)
The aim of the present study is to investigate the impact of multiple strategic orientations (entrepreneurial orientation and learning orientation) and strategic flexibility (coordination flexibility and resource flexibility) on product innovation in knowledge-based companies located in Kerman city. This research, in terms of methodology, is a descriptive-survey study (utilizing a standardized questionnaire), and in terms of purpose, it is applied research. The statistical population of this study includes all CEOs, financial managers, marketing managers, and production managers of knowledge-based companies situated in the Science and Technology Park of Kerman Province in the year 2022. The sampling method was purposive. The reliability of the aforementioned questionnaire was estimated at 0.904, and its content validity was confirmed by experts and academics. A total of 260 responses were collected through in-person surveys and were then analyzed using confirmatory factor analysis and structural equation modeling. For data analysis, SPSS version 24 and PLS version 3 software were employed. Our findings indicated that entrepreneurial orientation has a significant impact on learning orientation, coordination flexibility, and product innovation in knowledge-based companies. Moreover, learning orientation has a positive effect on coordination flexibility and product innovation. Additionally, the moderating role of resource flexibility in the relationship between coordination flexibility and product innovation was confirmed. Ultimately, coordination flexibility and learning orientation mediate the relationship between entrepreneurial orientation and product innovation. Based on the findings of this study, it is possible to identify the factors that influence product innovation under the current competitive conditions.